DIRECTIVE SPEECH ACT IN EXPRESSION OF MAGICAL POWER ON THE WALLS OF ELEMENTARY SCHOOL - Rani Setiawaty; Agus Budi Wahyudi; Atiqa Sabardila; Joko Santoso (Universitas Negeri Makassar, 2023)
This study aims to describe the form of directive speech act, mode, and function in expression of magical power on the walls of elementary school at Karesidenan Surakarta. This type of research is descriptive qualitative. The data are in the form of words, expressions, and sentences contained expression of magical power on the walls of elementary school at Karesidenan Surakarta. Analyzing data of the research uses referential equivalent, pragmatic, translational, and distribution methods of reading markup techniques. Collecting data uses the documentation method. The results show that first, the expression of magical power on the walls of elementary school at Karesidenan Surakarta indicate two forms of speech acts, namely direct speech act and indirect speech act. Second, the sentence mode used is the imperative mode, the obligative mode, and the declarative-imperative mode. Third, the existing speech act function consists of imperative mode (order, appeal, prohibiting, and invitation/exclamation), obligative mode functions to require, and declarative-imperative mode functions to assert, remind, advise, propose/offer/suggest, governing, and threatening. The novelty of this research found that the expression of magical power on the walls of elementary school generally uses an indirect strategy. The strategy is expressed through a declarative sentence but has an imperative mode with the aim of smoothing the command to the reader. It is intended that the reader follows the command in the expression of magical power on the walls of elementary school.